Comparison of elisa and intradermal skin test in atopy suspected dogs - Sibel Yasa Duru; Mehmet Şahal (Eurasian Journal of Veterinary Sciences)
Aim: In this study, it was aimed to determine whether application of ELISA and IDT to atopy suspected dogs give the same results using same allergens. In addition, determination of the most common allergens, dog breeds predisposed to atopy, age and gender of atopic dogs was aimed in Turkey. Materials and Methods: IDT applied to the most common allergens in the atopy suspected dogs according to the history and clinical symptoms. The blood samples, which are collected same dogs, determined level of asp IgE against the same allergens by ELISA. Results: ELISA and IDT were performed on 30 dogs (18 male and 12 female, 8 months and 9 years old) with suspected atopic dermatitis. Dermatophagoides farinae, Dermatophagoides pteronyssimus, Tyrophagus spp. and Acarus siro were most frequent in both tests, but male dogs (60%) were more effected than the female dogs (40%). Boxer and Terrier dogs were found to be predisposing to predilection of atopic dermatitis. In generally age of the dogs with AD ranged from 1 to 3 years old. Conclusion: Similar results can be obtained from ELISA and IDT, when the same allergens were used. But the severity of the results may be different and more questionable reaction can be observed with ELISA.